A polydrug regime for treatment of sudden sensorineural hearing loss - M., Muniraju; Killera, Shambulinga; Kauser, Safina (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Sudden sensorineural hearing loss (SSNHL) is a very frightening and incapacitating event and it impairs the patient's quality of life. Steroids are considered the first line of treatment. Intratympanic dexamethasone produces a significantly higher perilymph concentration of steroids. The aim of our study was to assess the efficacy of multi-drug regimen in the management of SSNHL, to analyse the recovery and to assess use of intratympanic steroid injections (ITSI) as a primary treatment. This is a prospective study presenting as a case series of 5 cases of SSNHL. Our treatment included intratympanic steroids, oral steroids, antiplatelet drugs, rheological-agents and neuro vitamins. Complete recovery was seen in 2 (40%), partial recovery in 2 (40%), 1 patient was lost to follow up. In the patient with bilateral SSNHL, the ITSI was administered in the right ear only; which showed a significant improvement. SSNHL is described as a decline in hearing of 30 dB or more, on 3 or more frequencies over 3 days or less, with tinnitus and ear fullness. Early presentation and intervention within 72 hours is the ideal treatment. Since viral infections and vascular compromise are considered as probable theories for SSNHL, steroids, with anticoagulants, antiplatelet and rheological-agents are used as an effective therapy. Our study shows that a multi-drug treatment of SSNHL can be much more effective than a single drug treatment. We also conclude that using intratympanic steroid injections have a greater improvement as seen in the case of bilateral SSNHL.